Dosimetry of cones for radiosurgery system - Furnari, Laura; Sales, Camila P.; Santos, Gabriela R.; Silva, Marco A.; Menegussi, Gisela (Revista Brasileira de Física Médica, 2015)
Dosimetry of small fields, such as cones for radiosurgery, requires a lot of care in its implementation. The acquisition of curves of Percentage depth dose (PDD) and profiles for nine circular cones with diameters from 4 to 20 mm for 6 MV photons was performed. Measurements with four types of dosimeters: diode, pinpoint ionization chamber, diamond detector and film were done. A comparison between the data obtained with the several detectors permitted to conclude that the diode is the detector more reliable. The effect of various methods to “smooth” the curves was studied and showed that there are methods that change very much the measured data. Interpolations were made in PDD curves in order to eliminate the noise of small fields due to low signal in the detectors. The most important conclusion refers to the choice of suitable detector, in this case the diode, and to a careful handling of obtained data to not disturb or modify the results of the measurements.